2021
DOI: 10.1037/sah0000230
|View full text |Cite
|
Sign up to set email alerts
|

An implication of impurity: The impact of feminine honor on human papillomavirus (HPV) screenings and the decision to authorize daughter’s HPV vaccinations.

Abstract: Due to the high prevalence of human papillomavirus (HPV) infections and their relationship with cervical cancer, it is of high interest to understand the processes that help (or hinder) women to receive HPV screenings. Unfortunately, prior research has demonstrated that due to the sexually transmitted nature of the infection, many women report a stigma of sexual impurity or promiscuity regarding HPV screening, which may prevent some women from seeking such screenings. While many women will experience stigma th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 93 publications
(118 reference statements)
5
20
0
Order By: Relevance
“…These findings add to a growing body of literature, which links honor endorsement to lower levels of help-seeking behaviors and likelihood to seek health procedures due to stigma (Brown et al, 2014; Crowder & Kemmelmeier, 2017; Foster, Carvallo, Lee, et al, 2020; Foster, Carvallo, Lee, & Bernier, 2020; Foster et al, 2021). Due to an individual’s worth in an honor culture stemming from what is externally recognizable, honor endorsers will be less likely to seek help in any context that would draw attention to potentially “dishonorable” personal qualities.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…These findings add to a growing body of literature, which links honor endorsement to lower levels of help-seeking behaviors and likelihood to seek health procedures due to stigma (Brown et al, 2014; Crowder & Kemmelmeier, 2017; Foster, Carvallo, Lee, et al, 2020; Foster, Carvallo, Lee, & Bernier, 2020; Foster et al, 2021). Due to an individual’s worth in an honor culture stemming from what is externally recognizable, honor endorsers will be less likely to seek help in any context that would draw attention to potentially “dishonorable” personal qualities.…”
Section: Discussionsupporting
confidence: 55%
“…This research reveals that honor endorsers are less likely to seek mental health help, in large part, due to their belief that seeking psychological help means admitting “weakness,” which would ultimately compromise their reputation in front of others (Brown et al, 2014; Crowder & Kemmelmeier, 2017). Similar findings have emerged in the field of sexual health, where honor-endorsing women were less likely to seek HPV and STI screening out of fear it would imply that they were promiscuous, thereby compromising their reputation (Foster, Carvallo, Lee, et al, 2020; Foster et al, 2021).…”
supporting
confidence: 69%
See 1 more Smart Citation
“…As in other honor-oriented cultures that exist in societies around the world, maintaining a reputation of self-reliance and willingness to partake in retaliatory aggression in response to insults and other reputation threats is paramount within the culture of honor in the U.S. (Brown, 2016). For men in cultures of honor, one strives to maintain a reputation of strength and virility (Brown et al, 2014), while for women, one’s reputation tends to center around sexual purity and loyalty (Foster et al, in press). For men and women in cultures of honor, strong reputational concerns drive the avoidance of dishonorable behavior, particularly given that one’s own honor, the honor of one’s partner, and the honor of one’s family tend to be linked together (McLean et al, 2018).…”
mentioning
confidence: 99%
“…For example, Foster and colleagues (2021b) found that women who strongly (vs. weakly) endorsed feminine honor values reported decreased intentions to schedule sexually transmitted infections screenings, because of their increased negative beliefs and emotions (e.g., shame) associated with the screening. In another study, Foster et al (2021b) also showed that the more women valued feminine honor, the less likely they were to receive human papillomavirus (HPV) screenings, because they expected to feel shame and embarrassment if they are screened. Moreover, women with strong (vs. weak) feminine honor values were less likely to get their daughters vaccinated against HPV, because of their belief that HPV vaccination may encourage promiscuity, demonstrating that honor values can shape not only people's own health-related choices but also those of close others'.…”
Section: Honor and Help-seeking For Mental And Physical Health Problemsmentioning
confidence: 99%